Building beyond earth: a roadmap for human-robot collaboration and workforce development in extraterrestrial construction - Jafari, Amirhosein; Gary-Bicas, Carlos E.; Qian, Yufeng; Webb, Andrew M.; Zhu, Yimin; Jamerson, Jason (Frontiers in Space Technologies, 2025)
Creating sustainable habitats on the Moon and Mars requires converging advances in construction technologies, human-robot collaboration (HRC), and workforce development. This paper synthesizes insights from a transdisciplinary workshop that focuses on three main themes: (1) trust-calibrated HRC systems for latency-laden and safety-critical tasks; (2) construction technology for extraterrestrial applications, for example, those challenges of dust mitigation, in-situ resource utilization (ISRU), and planetary protection; and (3) immersive and AI-assisted training that incorporates the necessary knowledge, skills, and abilities for the future-ready workforce. Participants involved in this transdisciplinary workshop identified regolith-based additive manufacturing, high-fidelity HRC testbeds, adaptive extended-reality (XR) training, and modular energy opportunities as near-term priorities. This study presents a converging roadmap that focuses on a series of prioritized, scalable steps over 1–15 years, incorporating technology, human, and ethical considerations to inform endeavors like the National Aeronautics and Space Administration (NASA) Artemis Program and the European Space Agency (ESA) Moon Village concept. The framework positions extraterrestrial construction as a socio-technical endeavor by providing actionable steps toward sustainable extraterrestrial habitation.